Blockwork laying an AAC block / Muhammad Zulhaziq Zulkurnain - Zulkurnain, Muhammad Zulhaziq (Universiti Teknologi MARA UiTM,Perak, 2022)
Blockwork is a wall or structure, or the act of producing such a structure using Autoclaved aerated concrete, is a lightweight, precast, foam concrete building material (AAC). The primary goal of this study is to cover blockwork for AAC block laying. This report was written for a renovation project in a three-story building at Politeknik Ungku Omar, where an old wood wall was to be replaced with an AAC block. The goal is to look at the process of laying an AAC block from beginning to end. This study will concentrate on the entire procedure of installing an AAC block. It will also look at the methods, equipment, and machines utilized during the process to see the differences between regular bricks and AAC blocks. This report will explain blockwork laying an AAC block.